Pengembangan Model Pengukuran Konstruk Kinerja Dosen Pendidikan Ekonomi Berdasarkan Persepsi Mahasiswa - Supriyanto, Supriyanto (Jurnal Aplikasi Manajemen, 2008)
The research was intended to verify the performance of economic education lecturer based on the perception of students. The population was all bachelor degree-economic education students of Economic Faculty at State University of Malang, which studied educational subjects at 2nd semester in 2007/2008. The amount of population was 607 students. The sample was selected based on the random sampling. The sample size was determined by using the Daniel-Terrel's formula. By using of that formula, 236 students were elected as sample. The Likert-five point scale was used as a research instrument. Furthermore, the data were analyzed by confirmatory factor analysis, to verify unidimensionality, composite reliability, and construct validity. In brief, the finding of research that the performance of economic education lecturer was validly reflected by the teaching implementation and the personality of lecturer in teaching